2016
DOI: 10.1007/s00464-016-5209-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal cancer resections in the obese: a systematic review

Abstract: Laparoscopic colorectal cancer operations in obese patients pose an increased technical challenge as demonstrated by higher conversion rates and higher risk of postoperative complications compared to non-obese patients. Despite these challenges, oncologic adequacy of laparoscopic colorectal cancer resections is comparable in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 53 publications
3
46
0
3
Order By: Relevance
“…Nevertheless, on the basis of these studies, it was difficult to determine whether or not LAC for obese patients was acceptable. To date, there have been no randomized-controlled trials comparing LAC and OC for colorectal cancer in obese patients, and only limited numbers of retrospective studies have been performed (6,9,11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, on the basis of these studies, it was difficult to determine whether or not LAC for obese patients was acceptable. To date, there have been no randomized-controlled trials comparing LAC and OC for colorectal cancer in obese patients, and only limited numbers of retrospective studies have been performed (6,9,11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of short-term outcomes, randomized controlled trials have generally shown advantages of the minimal invasiveness of LAC in terms of reduced blood loss, earlier recovery, and lower complication rates compared with those of open colectomy (OC). When the focus is obese patients, however, increased postoperative complications (6), reoperation rates (7) and conversion rates (8)(9)(10)(11) have been reported for LAC. A possible explanation for this inverse effect may be the technical difficulty in maintaining adequate surgical views in the presence of bulky visceral fat.…”
mentioning
confidence: 99%
“…A meta‐analysis (n = 4550) of laparoscopic surgery by Fung et al found that, for colorectal cancer surgery, SSI, leakage, morbidity, and conversion rate are significantly higher in patients with BMI > 30 than in those with normal BMI. Table shows a summary of past studies on the effects of obesity on outcomes of colorectal surgery.…”
Section: Colorectal Surgerymentioning
confidence: 99%
“…Because obesity is increasing globally, managing obese patients is clinically demanding. A recent systematic review showed that laparoscopic surgery for rectal cancer in obese patients is technically challenging because of the longer operative times, higher risk of postoperative complications, and higher rates of conversion to OS compared with non‐obese patients . Recent retrospective case‐control studies that compared obese versus non‐obese patients (body mass index of ≥30 vs <30 kg/m 2 , respectively) undergoing robotic colorectal surgery consistently showed no difference in the conversion rate, rate of CRM, intraoperative or postoperative complications, or length of hospital stay .…”
Section: Short‐term Outcomesmentioning
confidence: 99%